Mental training sessions between an eminent consultant and elite level athletes: A case study. - Lloyd, Rebecca Jane. (University of Ottawa (Canada), 1997)
A case study design was used to describe (a) an eminent mental training consultant's published approach to consulting, (b) the content and the process of the verbal interactions between an eminent mental training consultant and four elite level athletes during ten authentic mental training sessions, and (c) the congruencies between the consultant's published approach and the content and process of the mental training sessions. The sources of information were literature published by the consultant, audio recordings of the mental training sessions, interview with the consultant and interviews with the athletes. An inductive analysis was used with each source of information and an adapted version of the Flanders' (1965) Interaction Analysis in the Classroom was used to systematically code the process. The seven elements of excellence from Orlick's Wheel (1995) were apparent in the content of the sessions. Other categories that emerged were physical elements, injury, emotion, relations with others, transition, balance, competition, outcome, intensity, artistic presentation, money and audio/visual materials. During the sessions, the consultant's verbal behaviours accounted for 39% of the total coded behaviours were 21% were classified as indirect and 18% as direct. Sixty percent of the total coded behaviours wre the athletes responding, initiating or asking questions. One percent of the time was spent in silence. Both the analysis of the content and the process confirmed the consultant's athlete-centered approach to consulting. The comparison of the consultant's published approach with the analysis of the content and the analysis or the process of the mental training sessions indicated that the consultant actually did what he reported to do, i.e., follows an athlete-centered approach.
Keywords: Education, Physical.